Intrafirm Trade and Global Transfer Pricing Regulation (Book). - Larue, David W.; Williams, Thomas H. (The Accounting Review, 1998)
Abstract Reviews the book "Intrafirm Trade and Global Transfer Pricing Regulation," by Roger Y.W. Tang.